Trois études sur la tradition des commentaires anciens à la métaphysique d'Aristote - Luna, Concetta. (Philosophia Antiqua, 2001)
This volume discusses the relationship between the four extant ancient commentaries on Aristotle's Metaphysics of Alexander of Aphrodisias, Syrianus, Asclepius and Ps. Alexander. Comparative analysis of these commentaries allows Luna to attribute the Ps. Alexander to Michael of Ephesis and to show to what extend Syrianus made use of Alexander and Asclepius of both of them. The author draws up a precise genealogy of these Metaphysics commentaries. The book is indispensable for anyone working on the history of Aristotelian exegesis.